Rediscovering Secondary Tumors of the Prostate in the Molecular Era. (May 2016) - Fusco, Nicola; Sciarra, Amedeo; Guerini-Rocco, Elena; Marchiò, Caterina; Vignani, Francesca; Colombo, Piergiuseppe; Ferrero, Stefano
Abstract : Metastatic involvement of the prostate from noncontiguous solid tumors is a rare event occurring by means of vascular dissemination. The reported cases of biopsy and surgical samples with metastatic involvement have increased; however, a comprehensive understanding of secondary tumors of the prostate is currently missing. Metastases to the prostate carry a dismal prognosis and may pose serious diagnostic challenges to both clinicians and pathologists, with crucial therapeutic implications. Secondary tumors of the prostate spread more frequently from the digestive tract, the lung, and the kidney. The integration of clinicoradiologic data with appropriate pathologic and immunohistochemical analyses is essential for the identification and the characterization of secondary tumors of the prostate, whereas molecular analyses could provide additional and complementary information, enabling precise diagnosis and appropriate clinical management. Patients with solitary metastases could benefit from prostatic resection and adjuvant therapy, whereas in cases of disseminated diseases, symptom control may be obtained with palliative procedures. The purpose of this review was to assess the current state of knowledge of secondary tumors involving the prostate gland and to discuss short-term future perspectives, while providing a practical approach to these uncommon conditions for pathologists and oncologists.